2003
DOI: 10.1093/carcin/bgh029
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic-induced DNA hypomethylation affects chromosomal instability in mammalian cells

Abstract: Early genetic instability induced in dividing V79-Cl3 Chinese hamster cells by inorganic arsenic, as demonstrated in our previous investigation, was evidenced by aneuploidy and nuclear abnormalities, but not by chromosomal rearrangements. Here we report the results of cytogenetic and morphological analyses performed on the progeny of cells dividing at the end of sodium arsenite treatment after they had been expanded through 120 generations (ASO cells) and then cloned. The acquired genetic instability persisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(65 citation statements)
references
References 25 publications
1
62
0
2
Order By: Relevance
“…Effects observed just after treatment are aneuploidy and DNA methylation alterations (6). These findings are consistent with a non-mutagenic mode of action and are suggestive of indirect genotoxic mechanisms (7).…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Effects observed just after treatment are aneuploidy and DNA methylation alterations (6). These findings are consistent with a non-mutagenic mode of action and are suggestive of indirect genotoxic mechanisms (7).…”
Section: Introductionsupporting
confidence: 75%
“…Briefly, 3x10 6 exponentially growing astrocytes, immediately after the arsenite treatment, were washed twice with Hank's salt solution, collected by trypsinization and then incubated in the dark with 25 ÎŒM CM-H 2 DCFDA for 1 h. Finally, they were analysed by flow cytometer (FACScan Becton Dickinson), using excitation sources and filters appropriate for fluorescein (FITC). Treated and untreated cells were evaluated.…”
Section: Ros Detectionmentioning
confidence: 99%
“…A Glaviano et al Mothersill et al, 1998) or hypermethylation (Sciandrello et al, 2004) or adduct formation. In theory, the persistent increase of dicentric chromosomes in the hTERTÀ cells could have arisen in three ways.…”
Section: Metal-induced Genomic Instabilitymentioning
confidence: 99%
“…6 It has been shown that DNA methylation is important for maintaining centromeric chromatin stability and plays an important role in chromosomal segregation. 7,8 Polymorphisms of genes that encode enzymes involved in folate metabolism have been associated with the etiology of DS. [9][10][11][12] A polymorphism of the reduced folate carrier 1 (RFC1) gene consisting of an adenine-to-guanine substitution at position 80 (A80G) has been associated with altered concentrations of products derived from the folate metabolic pathway.…”
Section: Introductionmentioning
confidence: 99%